2018
DOI: 10.1016/j.anai.2017.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approach to the patient with refractory atopic dermatitis

Abstract: INSTRUCTIONSCredit can now be obtained, free for a limited time, by reading the review article in this issue and completing all activity components. Please note the instructions listed below:• Review the target audience, learning objectives and all disclosures.• Complete the pre-test.• Read the article and reflect on all content as to how it may be applicable to your practice.• Complete the post-test/evaluation and claim credit earned. At this time, physicians will have earned up to 1.0 AMA PRA Category 1 Cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…138 Before starting a systemic treatment, it is important to rule out differential diagnoses such as cutaneous T-cell lymphoma, potential trigger factors such as allergic contact dermatitis and behavioural and educational reasons for poor responses. 74,139 Until recently, rather broad-acting immunosuppressants, such as systemic corticosteroids (SCS), cyclosporine A (CyA), azathioprine (AZA), mycophenolate mofetil (MMF), enteric-coated mycophenolate sodium (EC-MPS) and methotrexate (MTX), were the only systemic treatment options for difficult-to-treat AD. 140 These systemic immunosuppressants can roughly be divided into two groups: SCS and CyA have a rapid onset of action and can be used to treat flares of AD or to bridge the time until onset of action of slow-acting systemic immunosuppressants such as MTX, AZA and MMF/EC-MPS.…”
Section: Systemic Anti-inflammatory Therapymentioning
confidence: 99%
“…138 Before starting a systemic treatment, it is important to rule out differential diagnoses such as cutaneous T-cell lymphoma, potential trigger factors such as allergic contact dermatitis and behavioural and educational reasons for poor responses. 74,139 Until recently, rather broad-acting immunosuppressants, such as systemic corticosteroids (SCS), cyclosporine A (CyA), azathioprine (AZA), mycophenolate mofetil (MMF), enteric-coated mycophenolate sodium (EC-MPS) and methotrexate (MTX), were the only systemic treatment options for difficult-to-treat AD. 140 These systemic immunosuppressants can roughly be divided into two groups: SCS and CyA have a rapid onset of action and can be used to treat flares of AD or to bridge the time until onset of action of slow-acting systemic immunosuppressants such as MTX, AZA and MMF/EC-MPS.…”
Section: Systemic Anti-inflammatory Therapymentioning
confidence: 99%
“…Wet dressings and short-term hospitalizations are other options for patients with severe, recalcitrant AD whose multiple therapies have failed. 9,53,54,[96][97][98] These treatments also are sometimes used for patients for whom treatment choices are limited due to costs and/ or insurer considerations. More information is provided in current guidance documents and several excellent reviews.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…More information is provided in current guidance documents and several excellent reviews. 9,53,54,[96][97][98]…”
Section: Other Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Our understanding of mechanisms that lead to AD must be considered in the management of this common skin disease. 11 Importantly, the focus on AD has shifted from exclusive evaluation of the skin lesion to changes that occur in nonlesional AD skin. 12 It has now been demonstrated that skin barrier abnormalities occur before the onset of clinical AD, supporting the concept that epicutaneous allergen sensitization with a predisposition to food allergy may occur very early in life.…”
mentioning
confidence: 99%